Seven new microcystin variants discovered from a native Microcystis aeruginosa strain – unambiguous assignment of product ions by tandem mass spectrometry. (16th December 2014) - Qi, Yulin; Rosso, Lorena; Sedan, Daniela; Giannuzzi, Leda; Andrinolo, Dario; Volmer, Dietrich A.
Abstract : RATIONALE: High‐resolution mass spectrometry was applied to the study of a Microcystis aeruginosa strain previously reported as a [D‐Leu 1 ]MC‐LR producer. Detailed analysis revealed new microcystin (MC) variants produced from the strain, and seven of these were previously unreported variants. This work shows the importance of mass accuracy for the identification of unknown MCs. METHODS: The M. aeruginosa strain was isolated from a bloom sample collected from Argentina and acclimated to lab conditions. The MC variants in the strain were separated by UV/Vis detection‐guided high‐performance liquid chromatography, and their structures were unambiguous determined by tandem mass spectrometry (MS/MS). RESULTS: A simple strategy was developed for quickly locating the low‐abundance MC precursors from complex samples. MS/MS anlysis revealed ten MC variants produced from the strain, of which seven have never been reported before. CONCLUSIONS: This work shows the interference of isobarics and isomers in the study of unknown MCs, and, therefore, high mass accuracy is important to avoid false assignments. Moreover, the peak list provided here (30–50 fragments unambiguously assigned for ten MCs) can be used as a reference for the discovery of MCs from environmental samples. Copyright © 2014 John Wiley & Sons, Ltd.